Exploring cooperative transboundary river management strategies for the Eastern Nile Basin - Wheeler, K; Hall, J; Abdo, G; Dadson, S; Kasprzyk, J; Smith, R; Zagona, E (Wiley, 2018)
A water resource modeling process is demonstrated to support multistakeholder negotiationsover transboundary management of the Nile River. This process addresses the challenge of identifyingmanagement options of new hydraulic infrastructure that potentially affects downstream coriparian nationsand how the management of existing infrastructure can be adapted. The method includes an explorationof potential management decisions using a multiobjective evolutionary algorithm, intertwined with aniterative process of formulating cooperative strategies to overcome technical and political barriers faced in atransboundary negotiation. The case study is the addition of the Grand Ethiopian Renaissance Dam (GERD)and considers how its operation may be coordinated with adaptations to the operations of Egypt’s HighAswan Dam. The results demonstrate that a lack of coordination is likely to be harmful to downstreamriparians and suggest that adaptations to infrastructure in Sudan and Egypt can reduce risks to water suppliesand energy generation. Although risks can be substantially reduced by agreed releases from the GERD andbasic adaptations to the High Aswan Dam, these measures are still insufficient to assure that no additionalrisk is assumed by Egypt. The method then demonstrates how improvements to water security for bothdownstream riparians can be achieved through dynamic adaptation of the operation of the GERD duringdrought conditions. Finally, the paper demonstrates how the robustness of potential managementarrangements can be evaluated considering potential effects of climate change, including increasedinterannual variability and highly uncertain changes such as increases in the future persistence of droughts.